Practicing psychodynamic therapy : a casebook - Summers, Richard F.; Barber, Jacques P.
"This volume presents 12 highly instructive case studies grounded in the evidence-based psychodynamic therapy model developed by Richard F. Summers and Jacques P. Barber. Bringing clinical concepts vividly to life, each case describes the patient's history and presenting problems and takes the reader through psychodynamic formulation, treatment planning, and the entire course of therapy, including the challenges of termination. The cases address a variety of core psychodynamic problems, with outcomes ranging from very successful to equivocal. The emotional experience of the therapist is explored throughout. Commentary from Summers and Barber in every case highlights important points and key clinical dilemmas. See also the authored book Psychodynamic Therapy: A Guide to Evidence-Based Practice, in which Summers and Barber comprehensively describe their therapeutic model"--